English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i need a step by step sloving this math problem so i can do the next one on my own. thanks

2007-02-01 05:24:51 · 6 answers · asked by ~tu mami~ 1 in Science & Mathematics Mathematics

6 answers

multiply out brackets:
-12x - 6 = -4x + 10
put x's on one side, numbers on the other:
-12x + 4x = 10 + 6
work out:
-8x = 16
divide by -8:
x = -2

2007-02-01 05:29:13 · answer #1 · answered by swisshorizon 2 · 0 0

x = -2

2007-02-01 05:46:25 · answer #2 · answered by Toy 2 · 0 0

-6(2x + 1) = -4x + 10

Step 1: distribute the -6
-12x - 6 = -4x + 10

Step 2: separate the variables and constants across the =

-12x (+ 4x) - 6 = -4x (+ 4x) + 10
-8x - 6 = 10
-8x - 6 (+ 6) = 10 (+ 6)
-8x = 16

Step 3: solve for x
-8x / -8 = 16 / -8
x = -2

Hope this helps!

2007-02-01 05:30:15 · answer #3 · answered by disposable_hero_too 6 · 0 0

x=-2

2007-02-01 05:30:52 · answer #4 · answered by babis michael 2 · 0 0

-12x - 6 = -4x + 10
x = -2

2007-02-01 05:27:58 · answer #5 · answered by Dan M 1 · 0 0

-12x-6=-4x+10
-12x-6+6=-4x+10+6
-12x=-4x+16
-12x+4x=-4x+4x+16
-8x=16
-8x/-8=16/-8
x=-2

2007-02-01 06:19:15 · answer #6 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers